Chemical Constituents of the Vietnamese Marine Sponge Gelliodes sp. and Their Cytotoxic Activities. Issue 9 (19th August 2020) - Ki, Dae‐Won; Kodama, Takeshi; El‐Desoky, Ahmed H.; Wong, Chin Piow; Nguyen, Hien Minh; Do, Kiep Minh; Thai, Quang Minh; Ton Nu, Lien Huong; Morita, Hiroyuki
Abstract: A new decenoic acid derivative, gelliodesinic acid, and a naturally new alkaloid, together with three known furanoterpenoids and two known indole alkaloids, were isolated from the MeOH extract of the marine sponge Gelliodes sp. collected in Vietnam. The chemical structures of the isolated compounds were determined by analyses of 1D‐ and 2D‐NMR and MS data and by comparisons of the data with those reported in the literature. The cytotoxicity assay against HeLa, MCF‐7, and A549 cancer cell lines revealed that the three known furanoterpenes exhibited cytotoxic activities with IC50 values ranging from 23.6 to 75.5 μM against the three cell lines, and that 1 H ‐indole‐3‐carboxylic acid showed cytotoxicity with an IC50 value of 89.2 μM against A549 cancer cell lines. Abstract :